LIVELIHOOD EMPOWERMENT AGAINST POVERTY IN THE UPPER WEST REGION, GHANA: THE DEFIES AND GRIEVANCE REDRESS MECHANISM - Fuseini, M. N. (UDS International Journal of Development, 2021)
Livelihood Empowerment Against Poverty (LEAP) is a social assistance initiative that aims to help people living in poverty and the needy change their condition. However, few studies have focused exclusively on defies and the grievance redress mechanism (GRM) associated with LEAP’s activity. GRM and LEAP defies are essential because they have the potential to reduce LEAP programme impacts. To this end, concurrent mixed methods was applied to study defies and GRM of LEAP. A total of 302 LEAP beneficiaries took part in the study. Data were gathered using a questionnaire and an interview guide. Chi-square, descriptive statistics, and thematic analysis were used to analyse the data. The major defies of LEAP were discovered to be related to beneficiary and administrative problems. Although GRM existed, it proved to be ineffective. Appropriate support and supportive programmes must be assured to ensure full benefits for beneficiaries, while defies under recourse must be dealt with quickly.